O papel modalizador dos adjetivos em redações do ENEM - Padilha, Marjorie Patricia (2020)
This dissertation is based on the relation between language and technology. Therefore, we understand that the language is a system of signs over which different symbolic forms are manifested (CASSIRER, 2001). For this reason, language mainly serves to live, as it is imbued with meaning (BENVENISTE, 1989). Because it is located in the area of knowledge, we consider that language is a technology, based on Cupani (2004) and Vieira Pinto (2005). Grounded on Dascal’s theory, we also intend to verify language as cognitive technology. From this, the digital tool Tropes is used to quantify the corpus. Thus, the present work discusses how adjectives contribute to the construction of argumentation in Enem’s textual productions of 2018 (National High School Examination). In this sense, we seek to verify how the adjectives relate to the notions of modality how this demonstrates the choice of certain elements over others in this textual genre. To mention the Enem essay genre, Bakhtin’s studies (2016) are mobilized. The studies of Saeed (2003), Ilari and Basso (2008) and Castilho (2005) are used to approach epistemic and deontic modal categories. From this approach, the focus involves the modal load that the adjective attributes to the text. For that, the theory of possible worlds, and, consequently, the notions of modal force, modal base and ordering source brought by Kratzer (2006) are used. This focus aims to show that the adjectives found in the texts are epistemic and deontic, and, through the analysis, we seek to highlight the argumentative force that this category grants to this specific type of text. Such verification is done based on degree parameters and comparison scales.